Meningkatkan Pendapatan Masyarakat Melalui Peran Ekonomi Kreatif Di Desa Durian Perspektif Ekonomi Islam - Syifaunisya, Fimalati; Albab, Ulil; Mawardi, Mawardi; Rasyad Al Fajar, Muhammad (widya balina, 2023)
In the processing of salted fish, there are still obstacles causing a lack of sales, so income does not meet expectations. The hope for processing salted fish is that it can be better managed so that sales can be maximized and income will be better. The type of research used in this research is field research. The data in this research was obtained from primary data and secondary data. The data collection techniques used were observation, interviews, and documentation. The research method uses qualitative methods. First research results, after processing salted fish, the community experienced an increase in income. Second, the factors that influence the increase in the creative economy are creativity and innovation. These two factors influence people's income levels. Third, the implications of the existence of the creative economy have a positive impact on society which increases people's income. Fourth, the processing of salted fish is from the Islamic economic perspective.